2010
DOI: 10.1007/s00265-010-0940-1
|View full text |Cite
|
Sign up to set email alerts
|

When rate maximization is impulsive

Abstract: Although optimal foraging theory predicts that natural selection should favor animal behaviors that maximize long-term rate of gain, behaviors observed in the laboratory tend to be impulsive. In binary-choice experiments, despite the long-term gain of each alternative, animals favor short handling times. Most explanations of this behavior suggest that there is hidden rationality in impulsiveness. Instead, we suggest that simultaneous and mutually exclusive binary-choice encounters are often unnatural and thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The disjunction between the observed discount factors and the fundamental facts of foraging behavior has been particularly salient to field biologists, ethologists, and foraging theorists, because they are in the habit of thinking in evolutionary terms (Kacelnik, 2003;Pavlic & Passino, 2010;Stephens & Anderson, 2001;Stephens, Kerr, & Fernández-Juricic, 2004). Because severe discounting ought to be strongly disfavored by natural selection, they are reluctant to accept at face value the notion that animals make such obviously poor choices in their daily lives.…”
Section: Evolutionary Theory Predicts Neutral Time Preferencesmentioning
confidence: 99%
See 4 more Smart Citations
“…The disjunction between the observed discount factors and the fundamental facts of foraging behavior has been particularly salient to field biologists, ethologists, and foraging theorists, because they are in the habit of thinking in evolutionary terms (Kacelnik, 2003;Pavlic & Passino, 2010;Stephens & Anderson, 2001;Stephens, Kerr, & Fernández-Juricic, 2004). Because severe discounting ought to be strongly disfavored by natural selection, they are reluctant to accept at face value the notion that animals make such obviously poor choices in their daily lives.…”
Section: Evolutionary Theory Predicts Neutral Time Preferencesmentioning
confidence: 99%
“…Thus, delays can be costly even if they pose no special self-control problem. For this reason, several scholars have suggested that animals may avoid delays in intertemporal choice because they wish to avoid the opportunity cost they carry, and not because they lack self-control (Bateson & Kacelnik, 1996;Blanchard et al, 2013;Kacelnik, 2003;Pavlic & Passino, 2010;Stephens & Anderson, 2001). …”
Section: External Validity Of the Intertemporal Choice Taskmentioning
confidence: 99%
See 3 more Smart Citations